KEPERCAYAAN SEBAGAI MEDIASI HUBUNGAN CORPORATE IMAGE TERHADAP LOYALITAS PELANGGAN MOBIL LOW MPV - Nurfarida, Iva Nurdiana; Dianawati, Eris (Fakultas Ekonomika dan Bisnis, Universitas Kanjuruhan Malang, 2016)
The program's cost environmentally friendly cars or Low MPV (LCGC) issued by the Indonesian government to bring the impact of the availability of consumer choices Indonesia to buy a car at a bargain price. The challenge is whether consumers have confidence that the car MPV although low cost but still quality. Nearly all car manufacturers to get the car with this type so that competition in the automotive business has become very competitive. This study aims to determine causality corporate image to build customer trust and customer loyalty Low MPV car. The study was conducted on customers of Toyota cars, with the number of respondents 150, using accidental sampling and technique using path analysis. The results that the corporate image has a direct influence on the increase in customer loyalty, as well as striving indirectly through increased customer confidence LCGC Toyota. Manufacturer Toyota has the advantage of the corporate image of the customer against Toyota is high, so the products LCGC Toyota produced can be accepted by consumers for consumers / customers have a loyalty to Toyota, meaning that the high corporate image car customers LCGCÂ Toyota lead to customer loyalty. Another result of this study that the corporate image is also able to increase customer confidence LCGC Toyota subsequent impact on improving customer loyalty, meaning that belief becomes a mediation of the causal relationship of corporate image on customer loyalty.